Apically extruded debris and irrigants during root canal instrumentation with TruNatomy and ProTaper Gold rotary file systems - (:unkn) unknown (My University, 2021)
Aim: The objective of this study was to evaluate the amount of apically extruded debris and irrigants produced by TruNatomy and ProTaper Gold in mandibular incisor root canals. Methodology: Forty mandibular incisors were instrumented using TruNatomy (Dentsply Sirona, Maillefer, Ballaigues, Switzerland) and ProTaper Gold (Dentsply Sirona, Maillefer, Ballaigues, Switzerland) rotary systems. Apically extruded debris and irrigants during instrumentation were collected into preweighed Eppendorf tubes and were assessed with an electronic scale. All the procedures were performed in a 35 °C hot water bath. The data were analyzed using the Shapiro-Wilk test and Mann-Whitney U test at a 5% significance level. Results: Both NiTi file systems investigated extruded debris from the apical foramen. According to the data, the TruNatomy group extruded significantly less debris and irrigant from the apical foramen than the ProTaper Gold group (p<0.05). Conclusions: All the instruments caused apical extrusion. The TruNatomy instruments extruded less debris and irrigants apically than the ProTaper Gold instruments
Keywords: DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Agar gel model; apical extrusion; debris; TruNatomy; ProTaper Gold; RECIPROCATING SINGLE-FILE; EXTRUSION; UNIVERSAL; Agar gel model; apical extrusion; debris; TruNatomy; ProTaper Gold